Various Profiles of tet Genes Addition to tet(X) in Riemerella anatipestifer Isolates From Ducks in China - Zhu, De-Kang; Luo, Hong-Yan; Liu, Ma-Feng; Zhao, Xin-Xin; Jia, Ren-Yong; Chen, Shun; Sun, Kun-Feng; Yang, Qiao; Wu, Ying; Chen, Xiao-Yue; Cheng, An-Chun; Wang, Ming-Shu (Frontiers in Microbiology, 2018)
To investigate tetracycline resistance and resistant genotype in Riemerella anatipestifer, the tetracycline susceptibility of 212 R. anatipestifer isolates from China between 2011 and 2017 was tested. The results showed that 192 of 212 (90.6%) R. anatipestifer isolates exhibited resistance to tetracycline (the MICs ranged from 4 to 256 µg/ml). The results of PCR detection showed that, 170 of 212 (80.2%) R. anatipestifer isolates possessed the tet(X) gene. Other genes, including tet(A), tet(M), tet(Q), tet(O), tet(B), and tet(O/W/32/O), were found at frequencies of 20.8%, 4.7%, 1.4%, 0.9%, 0.9%, and 0.5%, respectively. However, tet(C), tet(E), tet(G), tet(K), and tet(W) were not detected in any isolate. In these tet gene positive strains, 31 (14.6 %), 2 (0.9%), 5 (2.4%), 1 (0.5%), 3 (1.4%) were detected containing tet(A)/tet(X), tet(M)/tet(O), tet(M)/tet(X), tet(O)/tet(X) and tet(Q)/tet(X) simultaneously, respectively. One isolates, R131, unexpectedly contained three tet genes, i.e., tet(M), tet(O) and tet(X). Sequence analysis of the tet gene ORFs cloned from R. anatipestifer isolates confirmed that tet(A), tet(B), tet(M), tet(O), tet(Q) and an unusual mosaic tet gene tet(O/W/32/O) were present in R. anatipestifer. The MIC results of R. anatipestifer ATCC 11845 transconjugants carrying tet(A), tet(B), tet(M), tet(O), tet(O/W/32/O), tet(Q), and tet(X) genes exhibited tetracycline resistance with MIC values ranging from 4 to 64 µg/ml. Additionally, the tet(X) gene could transfer into susceptible strain via natural transformation (transformation frequencies of 10-6). In conclusion, the tet(A), tet(B), tet(M), tet(O), tet(O/W/32/O), tet(Q), and tet(X) genes were found and conferred tetracycline resistance in R. anatipestifer isolates. Moreover, the tet(X) is the main mechanism of tetracycline resistance in R. anatipestifer isolates. To our knowledge, this is the first report of tet(A), tet(B), tet(M), tet(O), tet(Q) and mosaic gene tet(O/W/32/O) in R. anatipestifer.